Traditional birth attendants in Malawi - J. J. M. Smit (AOSIS, 1994)
Traditional Birth Attendants (TBAs) and traditional healers form an important link in the chain of health personnel providing primary health care in Malawi. In spite of the establishment of hospitals and health centres, it is to these traditional healers and TBAs that the majority of people turn in times of sickness and child-birth. Approximately 60 percent of all deliveries in Malawi occur in the villages. It is therefore important that due regard be paid to the activities of these traditional practitioners in order to ensure the achievement of the goal - "Health for all by the year 2000". The training of TBAs is seen as part of the Maternal and Child Health Services in the country.